Specific targeting of membrane nodulins to the bacteroid-enclosing compartment in soybean nodules - Fortin, Marc G. (1985)
Rhizobium bacteroids in nodule cells are surrounded by the peribacteroid membrane (pbm), which is derived from the host plasma membrane during infection. The pbm was purified from R. japonicum 61A76-induced soybean nodules and analyzed by comparing it with the host cell plasma membrane for the presence of nodulins, nodule-specific plant proteins. Nodulins were found in pbm by reacting Western blots with a nodule-specific antiserum raised against the pbm. Peribacteroid fluid (the fluid enclosed in the pbm) was also found to contain several nodulins. The pbm nodulins were confirmed to be of plant origin by in vitro translation of poly(A)(+) nodule mRNA followed by immunoprecipitation by the nodule-specific antiserum. Antibodies raised against a synthetic peptide corresponding to a repeated domain in nodulin-24, a pbm nodulin, and the nodule-specific pbm antiserum reacted exclusively with the pbm. The absence of pbm-nodulins in the plasma membrane suggests that the infected cells direct the intracellular transport of the pbm nodulins exclusively to this de novo synthesized subcellular compartment essential for symbiotic nitrogen fixation.